2016
DOI: 10.1590/1516-3180.20161346t1
|View full text |Cite
|
Sign up to set email alerts
|

Statins for aortic valve stenosis

Abstract: Result findings showed uncertainty surrounding the effect of statins for aortic valve stenosis. The quality of evidence from the reported outcomes ranged from moderate to very low. These results give support to European and USA guidelines (2012 and 2014, respectively) that so far there is no clinical treatment option for aortic valve stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Calcific aortic valve disease (CAVD) is the most common heart valve disease and the principal cause of aortic stenosis (AS) in Western countries. Angiotensin converting enzyme (ACE) inhibitors have shown some promise but their efficacy in counteracting the progression of AS in the clinical setting is still uncertain [1,2], while statins, although able to counteract calcification in vitro, were found to be ineffective in large randomized clinical trials [3,4]. Currently, there is no pharmacological therapy specifically indicated for CAVD, which progresses rapidly, eventually requiring the replacement of the aortic valve.…”
Section: Introductionmentioning
confidence: 99%
“…Calcific aortic valve disease (CAVD) is the most common heart valve disease and the principal cause of aortic stenosis (AS) in Western countries. Angiotensin converting enzyme (ACE) inhibitors have shown some promise but their efficacy in counteracting the progression of AS in the clinical setting is still uncertain [1,2], while statins, although able to counteract calcification in vitro, were found to be ineffective in large randomized clinical trials [3,4]. Currently, there is no pharmacological therapy specifically indicated for CAVD, which progresses rapidly, eventually requiring the replacement of the aortic valve.…”
Section: Introductionmentioning
confidence: 99%
“…13 Some observational studies suggested that statin therapy may slow the progression of AVC. 32,33 A meta-analysis of 4 randomized controlled trials found no differences in the clinically relevant outcomes such as mean pressure gradient, valve area, freedom from valve replacement and death from cardiovascular causes between the statin group and the placebo group, 34 but the authors of the meta-analysis stated that "this issue is not over, mainly because the available evidence is based on studies which have limitations such as follow-up, randomization process, sample size and very elderly participants with many comorbidities". Indeed, the analyzed patients (n=269) in the meta-analysis had a mean age of 58 years, with asymptomatic mild aortic valve stenosis defined by maximum aortic valve velocity of 2.5-4.0 m/s.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is compatible with former studies showing no impact of statins on AS progression [ 25 , 26 ]. Recently, Thaigo et al presented a review showing lower values of P mean in patients who were under statin therapy, but they also agree the analyzed studies did not have high quality and concluded that the role of statin therapy in AS remained uncertain [ 27 ]. CRP values were also high in the slow progression group indicating increased inflammatory stress in these patients; this could be fairly explained by the increased inflammation status and higher comorbidities in these patients.…”
Section: Discussionmentioning
confidence: 99%